Sistem Informasi Penjualan Kerajinan Tangan Berbasis Android - Adi prasetia nanda; aly hapiz; syaiful isnandar (Jurnal Multimedia dan Android (JMA), 2020)
Abstract Now a day, technology have  become a necessity in daily life. It has develop rapidly all around the world.Therefore, this technology, especially web technology and internet can be use to be a marketing medium that very helpful in sale process to reach broader general consumers that not limited by distance and time.This Web-Based Handicraft Sales Application aims to facilitate the work of Employees in the cashier, warehouse and management to do a sales and purchases the goods like handicrafts, payment of goods to suppliers, oversee the running of work systems and  also determine the next steps of the data presented.Last, with the use of this database system, the process of making web-based handicraft sales system which will be made computerized to get information simply, quicly, and accurately will be easier.By using this database system, the process of making web-based handicraft sales system which will be made computerized will be easier to get the information simply, quckly, and accurately. Keywords : Handicraft, system information, website Abstrak Masalah Teknologi telah menjadi kebutuhan di dalam kehidupan sehari-hari. Seperti pada saat ini dimana teknologi terbilang berkembang dengan pesat. Dengan melihat perkembangan teknologi web dengan internet sebagai media pemasaran sangat membantu proses penjualan guna menjangkau konsumen umum yang lebih luas dan tidak dibatasi oleh waktu dan jarak.Aplikasi Penjualan Kerajinan Tangan Berbasis Web ini bertujuan untuk memudahkan kerja Pegawai di bagian kasir, gudang dan management untuk melakukan transaksi penjualan maupun pembelian barang berupa kerajinan tangan, pembayaran barang kepada supplier, mengawasi jalannya sistem kerja serta dapat menentukan langkah selanjutnya dari data yang disajikan dan Dengan adanya system database, akan memudahkan dalam pembuatan Sistem penjualan Kerajinan Tangan berbasis Web yang akan dibuat secara komputerisasi untuk mendapatkan informasi dengan mudah, cepat dan akurat Kata Kunci : kerajinan tangan, sistem informasi, website